2011
DOI: 10.1111/j.2040-0209.2011.00377_2.x
|View full text |Cite
|
Sign up to set email alerts
|

Competition and Cooperation between Europe and China in the Wind Power Sector

Abstract: Summary This paper uses a value chain lens to examine the prospects for competition and cooperation between Europe and China in the global wind power sector. Drawing on insights from fieldwork conducted in 2010 combined with secondary industry data, we find that Chinese and European industries are developing distinct models of industrial‐technological organisation. The usual headlines emphasising Sino‐European competition or conflict fail to capture the complexity of current reality. While competition among le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 22 publications
1
33
0
Order By: Relevance
“…The supply chain for components is well-developed in China (Lema et al, 2011), although interviewees indicated that this was mostly true for turbines up to 1.5 MW. It is difficult to determine how 'truly domestic' this supply China is as many foreign component manufactures have production facilities in China.…”
Section: A 'Truly Domestic' Innovation Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The supply chain for components is well-developed in China (Lema et al, 2011), although interviewees indicated that this was mostly true for turbines up to 1.5 MW. It is difficult to determine how 'truly domestic' this supply China is as many foreign component manufactures have production facilities in China.…”
Section: A 'Truly Domestic' Innovation Systemmentioning
confidence: 99%
“…The biggest difference between these markets and the Chinese market is level of quality demanded (interviews, Lema et al, 2011, see also Section 6.2). A number of project managers who focused on the global market that we interviewed indicated that these quality demands are expressed in project development finance conditions.…”
Section: Foreign Market Expansionmentioning
confidence: 99%
“…So far, research and literature have largely analysed the European wind turbine industry and the global value chain for wind energy as seen from a Northern perspective (Karnøe and Buchhorn, 2010;Lema et al, 2011;Lema et al, 2013). Europe has traditionally played a lead role as an innovation hub in the development of modern wind turbines.…”
Section: ) What Factors Determine Strategies Of Internalisation and Ementioning
confidence: 99%
“…Chen et al (2014) shows how these firms access technology through engaging in collaborative ties across geography, e.g. within China and globally (Chen et al, 2014;Lewis, 2013;Silva and Klagge, 2014;Kirkegaard, 2015), and Lema et al (2011) have analysed the potential for collaboration between European and Chinese actors. Their studies show how the Chinese market has become a driver for reshaping the dynamics of the industry (Lema et al, 2011).…”
Section: Introduction: Configuration Of Technology and Innovation Netmentioning
confidence: 99%
See 1 more Smart Citation